Building a platform for success: How to develop products in an unpredictable environment. Issue 5 (8th April 2014) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Designing products using shared platforms is increasingly perceived as an effective means of remaining competitive within an unpredictable business environment. Product platforms help enhance strategic flexibility and better position firms to respond to different challenges. Attaining both short-and longer-term performance improvements are possible. Practical implications: – This paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to digest format.